Review of Climate Change Adaptation Towards Drinking Water and Sanitation in Nagarjun Municipality, Kathmandu District Nepal - Subedi, Dipak Kumar; Shrestha, Rajesh; Yadav, Punya Pratap (Patan Prospective Journal, 2022)
Climate change is difference in earth’s climate over time; it is largely caused by human activities which causes a serious threat to nature and people now and in the future too. Global temperature increased rapidly by four degrees Celsius. Climate change effects the water cycle and precipitation. Due to higher average temperatures and warmer air that can hold too much water, which can cause heavy precipitation and possible flooding. Nagarjun is the municipality which lies in the Kathmandu District (Bagmati Pradesh) of Nepal. It consists of Village development committees, Bhimdhunga, Ichangu Narayan, Ramkot, Syuchartar and Sitapaila. Nagarjun Municipality has in total 67420 populations along with 16746 households. The Major sources of drinking water are public water supply, well, springs and stream water. It depends on the sewer system more than half population able to access it but it has lack of treatment facilities for waste water and faecal sludge. These things are directly discharge through Manmati and Bhadramati Rivers.